APPLICATION OF LAVENDER AROMATHERAPY WITH INHALATION METHOD TO OVERCOME SLEEP PATTERN DISTURBANCES IN CHILDREN WITH CHRONIC KIDNEY DISEASE - Marshella Tri Pradilaga; Zesi Aprillia (Department of Nursing, Faculty of Medicine, Universitas Sriwijaya, 2025)
Chronic Kidney Disease (CKD) is a major global health problem due to the high number of sufferers and deaths from CKD. In children with end-stage CKD, permanent kidney damage requires partial renal excretory replacement therapy, such as hemodialysis. Children undergoing hemodialysis often experience sleep cycle disturbances. One form of non-pharmacological therapy that can be applied is aromatherapy with inhalation methods. This article describes the results of pediatric nursing practice that focuses on nursing care for children with CKD and is in accordance with evidence-based practice reviews. The method used is a descriptive case study approach in three pediatric clients with CKD who have sleep pattern disturbances. In this case study, seven nursing problems were found in the three clients: sleep pattern disturbances, hypervolemia, acute pain, decreased cardiac output, risk of ineffective renal perfusion, risk of infection, and risk of nutritional deficits, with the main nursing problem being sleep pattern disturbances. The results of the evaluation of sleep pattern disturbances in the three patients after being given aromatherapy with inhalation methods for three consecutive days showed an improvement in sleep quality as measured by a sleep quality questionnaire. The application of lavender aromatherapy as a non-pharmacological therapy has an effect on improving sleep quality in children with sleep pattern disorders, so it can be concluded that the application of lavender aromatherapy with the inhalation method is effective in overcoming sleep pattern disorders in children.